Dismantling the patriarchy, bit by bit art, feminism, and digital technology - Brodsky, Judith K. (London, UK Bloomsbury Visual Arts, 2023)
"In Dismantling the Patriarchy, Bit by Bit, Judith K. Brodsky makes a ground-breaking intellectual leap by connecting feminist art theory with the rise of digital art. Technology has commonly been considered the domain of white men but-unrecognized until this book-female artists, including women artists of color, have been innovators in the digital art arena as early as the late 1960s when computers first became available outside of government and university laboratories."--Page [4] of cover.
Introduction -- 1. Reinserting Women into the History of Digital Art: Pioneer Feminist Artists -- 2. The 1970s: Feminism and Digital Art Inside and Outside the Academy -- 3. Reimagining the Binary Nature of Digital Technology -- 4. Using Websites and Browsers to Deliver Social Justice Messages -- 5. Provoking the Patriarchy Through Digital Language -- 6. Queerness, Race, and Digital Art -- 7. The Avatar -- 8. The Female Body Disappears -- 9. Creating Feminist Paradigms of Knowledge through Digital Technology -- 10. Surveillance -- 11. Feminist Artists and the Gaming Industry -- 12. Japanese Feminism, Video Games, and Anime -- 13. Artificial Intelligence, Facial Recognition, and Virtual Reality -- 14. Digital Public Art and Augmented Reality -- Conclusion.
Includes bibliographical references (pages [215]-244) and index.
Keywords: Feminism and art -- 21st century; Women artists -- 21st century; Art and society -- 21st century; Art and technology -- 21st century; Art and computers -- 21st century; Virtual reality in art -- 21st century; Computer art -- Social aspects -- 21st century; Feminist ethics -- In art; Feminist aesthetics -- 21st century